Association of severity features and laboratory biomarkers with adverse maternal outcomes in pre-eclamptic women: a retrospective cohort study in an Ethiopian tertiary hospital - Hiluf Ebuy Abraha; Hale Teka (BMJ Open)
Objective To examine the association between clinical severity features, laboratory biomarkers and adverse maternal outcomes in women diagnosed with pre-eclampsia–eclampsia syndrome.Design A retrospective cohort study design.Setting Ayder Comprehensive Specialized Hospital, a tertiary care hospital in Tigray, Ethiopia.Participants A total of 1095 women diagnosed with pre-eclampsia–eclampsia syndrome between 2015 and 2021 were consecutively included.Outcomes Adverse maternal outcomes, defined as a composite of intensive care unit (ICU) admission, need for haemodialysis, pulmonary oedema or death.Methods A multivariable binary logistic regression model was used to assess the association between pre-eclampsia severity features, laboratory biomarkers and adverse maternal outcomes. Adjusted odds ratios (AORs) were estimated with 95% CIs.Results Adverse maternal outcomes occurred in 100 (9.1%) of cases. Eclampsia (AOR=8.85, 95% CI 4.08 to 19.20), lower extremity oedema (AOR=2.28, 95% CI 1.06 to 4.90) and elevated creatinine levels (AOR=5.07, 95% CI 2.21 to 11.61) were significant predictors. Additionally, increasing maternal age was associated with a higher risk (AOR=1.07, 95% CI 1.00 to 1.13).Conclusions Clinical severity features (eclampsia and lower extremity oedema), laboratory biomarkers (elevated creatinine) and increasing maternal age were associated with unfavourable maternal outcomes. These findings highlight the importance of integrating clinical signs and laboratory biomarkers into risk assessment for pre-eclampsia patients.